Knowledge of Hazards Associated With Urban Livestock Farming in Southeast Nigeria - Asadu, Anthonia N.; Chah, Jane M.; Attamah, Clement O.; Igbokwe, Edwin M. (Frontiers in Veterinary Science, 2021)
The study assessed urban farmers’ knowledge of health hazards associated with ULF in Southeast Nigeria Multistage and random sampling techniques were used to select 210 respondents. Structured interview schedule was used to collect data. Data collected was analyzed using descriptive and inferential statistics. Major type of animals reared was broiler. A good proportion of the respondents had a high knowledge of hazards associated with livestock keeping. However, a high of the respondents did not know that livestock contributes to climate change. There was a significant influence of socio-economic characteristics of farmers on the knowledge of hazards posed by livestock keeping. A significant variation was observed in the knowledge of hazards associated with urban livestock keeping, among urban farmers in the three states of southeast Nigeria studied. It is necessary to create awareness, so that farmers know the contributions of livestock to climate change and therefore take necessary precautions.